Milk Fat Globule-Epidermal Growth Factor-8 Pretreatment Attenuates Apoptosis and Inflammation via the Integrin-β3 Pathway after Surgical Brain Injury in Rats - Xiao, Yicai; Li, Gaofeng; Chen, Yujie; Zuo, Yuchun; Rashid, Kauthar; He, Tibiao; Feng, Hua; Zhang, John H.; Liu, Fei (Frontiers in Neurology, 2018)
Iatrogenic brain injury inevitably occurs in neurosurgical operations, leading to brain edema, ischemia, intracranial hematoma, and other postoperative complications, eventually worsening neurological outcomes of patients. If apoptotic cells are not rapidly eliminated by phagocytic engulfment, they may communicate with surrounding cells to undergo secondary necrosis and releasing toxic signals. Recent studies have shown that MFGE8, which promotes phagocytosis and inhibits inflammation, is an endogenous protective factor in response to brain infarction, Alzheimer’s disease, subarachnoid hemorrhage, and prion disease. In the present study, we sought to investigate the different effects of both pretreated- and posttreated- rhMFGE8 for the surgical brain injury (SBI) rat model and potential involvement of its receptor Integrinβ3 for apoptosis and neuroinflammation after SBI. One hundred and sixty-seven male rats were employed in the preset study. Experiment 1 was performed to evaluate neurological scores and MFGE8, cleaved caspase-3 (CC3) and Interleukine-1 beta (IL-1β) levels at 3, 24 and 120 h after SBI. Experiment 2 was performed to evaluate the effects of rhMFGE8 pretreatment (10 min before SBI) and rhMFGE8 post-treatment (6 h after SBI) on brain edema at 24 and 72 h after SBI. Experiment 3 was performed to evaluate the potential anti-apoptotic and anti-inflammatory effects of rhMFGE8 pretreatment and post-treatment. Experiment 4 sought to investigate the involvement of the integrin β3 signal in the effects of MFGE8 pretreatment. Our data showed rhMFGE8 pretreatment alleviated neurological deficits and decreased brain water content and apoptotic cells in the SBI model, which exhibited neurological dysfunction, apoptosis and inflammation. Meanwhile, MFGE8 siRNA, which inhibited endogenous MFGE8 expression, significantly increased IL-1β, TUNEL positive cells and cleaved caspase-3. Furthermore, knockdown of its receptor integrin β3 by siRNA abolished the effects of rhMFGE8 in the SBI model. In conclusion, we found that rhMFGE8 pretreatment effectively alleviated neurological deficits and decreased brain water content and apoptotic cells in the SBI model through the MFGE8/integrinβ3 pathway, and treatment time was an important factor in achieving curative effects. Therefore, MFGE8 pretreatment may serve as a promising therapeutic strategy for SBI patients.